Determinant Factors of E-Learning Adoption in Higher Education: A Systematic Review and Contextual Study of PEGASUS at Palembang Tourism Polytechnic - Irvan Setiadi; Alek Wijaya (Educia Journal, 2026)
The rapid digitalization of higher education has increased the importance of understanding the factors that influence e-learning adoption, particularly within vocational and tourism-oriented institutions. This study aims to identify and synthesize the key determinants of e-learning adoption in higher education and to contextualize these findings for the implementation of the PEGASUS platform at Palembang Tourism Polytechnic. A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Relevant studies published between 2015 and 2025 were retrieved from major academic databases, including Scopus, Web of Science, ERIC, Google Scholar, and ScienceDirect. A total of 47 eligible studies were selected and analyzed using thematic synthesis. The findings reveal that e-learning adoption is influenced by four interconnected dimensions: technological, individual, social, and organizational factors. Individual factors emerged as the most influential determinants, with performance expectancy and effort expectancy identified as the strongest predictors of adoption. Technological infrastructure, accessibility, and system quality were found to be essential enabling conditions, while social influence and institutional support significantly shaped users’ acceptance and continued use of e-learning systems. The review also highlights the unique challenges faced by tourism education institutions, where practical training, experiential learning, and interpersonal skill development limit the effectiveness of fully online learning environments. Consequently, blended learning is identified as the most suitable approach for tourism higher education. The study concludes that successful e-learning adoption requires not only technological readiness but also organizational capability, strategic leadership, and continuous capacity building. These findings provide practical insights for strengthening digital transformation initiatives and optimizing the implementation of PEGASUS at Palembang Tourism Polytechnic.